Acute Renal Failure due to Bladder Injury after Cesarean Section: Case Report and Review of the Literature - AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; KOÇ, MEHMET; TUĞLULAR, ZÜBEYDE SERHAN (TURK NEFROLOJI DIYALIZ TRANSPLANTASYON DERGISI, 2019)
A 31-year-old woman who had an uncomplicated cesarean section five days prior to admission presented with abdominal distention. Evaluation revealed acute renal failure and abdominal ascites. Diagnostic paracentesis showed urinary ascites, which confirmed a bladder injury. The patient was conservatively treated by placement of a Foley catheter that resulted in complete resolution of the renal failure.
Keywords: Acute renal failure; bladder injury; cesarean section